Soil loosening and drainage of structurally unstable silty soils - Twomlow, Stephen J.; Parkinson, Robert J.; Reid, Ian (Journal of hydrology (Amsterdam), 1990)
Secondary drainage treatments are carried out with the objective of enhancing the performance of permanent piped schemes. In this study, a drainage experiment was designed to investigate the effect of soil loosening on storm water redistribution in a structurally unstable silt soil following the installation of underdrainage. Results show that even though loosening reduced dry bulk density between 0.2 and 0.4 m depth by 15%, with a 270% increase in transmission pores (> 60 μm equivalent diameter) at the interface of what was the cultivated and undisturbed soil, drainage efficiency was not enhanced, as might have been expected from the 10- to 20-fold increase in hydraulic conductivity. Loosening not only lengthens the median time of concentration by 0.42 and 0.33 h for simple and secondary winter storms, respectively, but also caused lower peak discharges when compared with unloosened soil. Measurements of soil water energetics reveal that a greater proportion of rainfall is diverted into the loosened zone below the plough layer and detained there, reducing the 24 h drainage efficiency. On a seasonal timescale, the greater storage between 0.2 and 0.4 m depth causes a 6.3% increase in the winter mean water content, and means that the rooting environment of the loosened soil is wetter prior to a rainstorm. Consequently, in wet autumns and springs, loosened soils will be more susceptible to structural damage by animal poaching or the traffic of farm machinery.